Life Cycle Assessment on Global Warming and Fine Particulate Matter Formation for Biological Extraction Method in Polyhydroxyalkanoates (PHA) Production: A Sustainable Alternative - Iqbal Hakim Abd Razak; Zhen Xin Phuang; Kok Sin Woon; Kumar Sudesh (Chemical Engineering Transactions)
The production of polyhydroxyalkanoates (PHA), a promising class of biodegradable polymers, faces significant challenges due to the high costs associated with its downstream processing. Traditional methods for extracting PHA from microbial biomass are often expensive and environmentally taxing, involving the use of solvents and incalcitrant chemicals. There is a growing interest in developing non-conventional methods for PHA extraction to address these issues, such as utilizing insect model for the biological extraction of PHA. This method can potentially reduce costs, but its environmental feasibility is not inspected from a life cycle perspective. This study aims to evaluate the environmental impacts and identify the environmental hotspots of the biological extraction method in the PHA production with a focus on global warming (GW) and fine particulate matter formation (PMF) impacts using a life-cycle assessment (LCA) approach. The environmental impact of PHA production was assessed using the ReCiPe 2016 Midpoint (H) method, and results indicate that the biological extraction significantly contributes to GW (4.59 CO2-eq/kg of PHA) and PMF (4.59×10-3 PM2.5-eq/kg of PHA), with steam used in drum drying process identified as major contributing activity. By addressing these environmental hotspots, the sustainability and environmental performance of biological extraction in PHA production can be significantly improved. These findings highlight the potential for biological extraction to contribute to more sustainable PHA production at an industrial scale, which could benefit stakeholders involved in PHA production.